Theoretical Foundations of Adaptive Performance in Early Career Transition: Integration of Talent Identity Threat Perspectives, Learning Goal Orientation, and Government Career Context in Indonesia - Ayu Ambarwati; Ida Farida (Eduvest - Journal of Universal Studies, 2026)
The contemporary work environment is characterized by rapid change, uncertainty, and increasing complexity, requiring employees to demonstrate strong adaptive performance, particularly during early career transitions. In Indonesia, the growing interest of university graduates in careers within the State Civil Apparatus (ASN) creates unique challenges, as young employees must adapt simultaneously to bureaucratic structures, organizational expectations, and public service demands. This study aims to analyze the theoretical foundations of adaptive performance in early career transitions by integrating the perspectives of learning goal orientation, career adaptability, identity threats, and the Indonesian government career context. This research employed a qualitative approach using an integrative literature review design. Data were collected from scholarly articles, academic books, government reports, and empirical studies indexed in reputable databases, such as Scopus and Google Scholar. The collected data were analyzed using thematic analysis and integrative synthesis techniques to identify relationships among key concepts and contextual factors influencing adaptive performance. The findings indicate that learning goal orientation plays a significant role in strengthening career adaptability, buffering transition shocks, supporting identity construction, and enhancing resilience among early-career employees. In addition, organizational support, mentoring systems, and an adaptive bureaucratic culture significantly influence successful career transitions. This study concludes that adaptive performance in the Indonesian government sector is shaped by the interaction between individual motivational orientation, organizational context, and identity management processes, emphasizing the importance of continuous learning and supportive talent management systems.